Corrigendum to “Revisiting the modifiable areal unit problem in the era of exposome-wide association studies: Assessing the performance of the CDC/ATSDR social vulnerability index at privacy-protecting spatial scales” [Environ. Res. (2026) 124912] - Jonathan V. Lewis; Nathaniel MacNell; Ian D. Buller; Gary Larson; David Fargo; Charles P. Schmitt; Lawrence S. Kirschner; David M. Reif; Farida S. Akhtari; Cristina M. Justice; John S. House; Kyle P. Messier; et al. (Environmental Research, 2026)

Corrigendum to “Revisiting the modifiable areal unit problem in the era of exposome-wide association studies: Assessing the performance of the CDC/ATSDR social vulnerability index at privacy-protecting spatial scales” [Environ. Res. (2026) 124912] - Jonathan V. Lewis; Nathaniel MacNell; Ian D. Buller; Gary Larson; David Fargo; Charles P. Schmitt; Lawrence S. Kirschner; David M. Reif; Farida S. Akhtari; Cristina M. Justice; John S. House; Kyle P. Messier; et al. (Environmental Research, 2026)

Revisiting the modifiable areal unit problem in the era of exposome-wide association studies: Assessing the performance of the CDC/ATSDR social vulnerability index at privacy-protecting spatial scales - Jonathan V. Lewis; Nathaniel MacNell; Ian D. Buller; Gary Larson; David C. Fargo; Charles P. Schmitt; Lawrence S. Kirschner; David M. Reif; Farida S. Akhtari; Cristina M. Justice; John S. House; Kyle P. Messier; et al. (Environmental Research, 2026)

Multi-media occurrence, bioaccumulation, and exposure assessment of PFAS across a Midwestern U.S. State - Maria S. Sepúlveda; Lisa Brown; Staci L. Capozzi; Samantha C. Cullom; Jeffrey E. Dick; Daniel J. Foti; Ronaldo H. Franjul; Nicole L. Franklin; Jennifer L. Freeman; Carolina Gonzalez-Canas; Wanyue Hui; Yuxin Jiang; et al. (Environmental Research, 2026)

Environment and phytoplankton relative abundances in a hypersaline lake: 27 years in Great Salt Lake, USA and experiments - Gary E. Belovsky; Chad Larson; Younjin Han; Richard Wilson; Hannah J. Appiah-Madson; Heidi Mahon (Aquatic Ecology, 2025)
Over 27 years in Great Salt Lake (GSL: Utah, USA), phytoplankton relative abundances of chlorophytes, diatoms and cyanobacteria varied dramatically (monthly > 90%) of several of the most common GSL phytoplankton (chlorophyte– Dunaliella viridis , diatom– Nitzschia epithemioides , cyanobacterium– Euhalothece sp.). Maximum abundances and growth rates were measured across ranges of temperature (10–30 °C), salinity (30–150 ppt) and nutrients (nitrogen: 0.0–0.64 mg/L, silica:17–51 mg/L) observed within GSL. Experimental results indicated the abundance and growth rate of D. viridis increased as salinity and nitrogen increased and decreased as temperature increased. The abundances and growth rates of N. epithemioides and Euhalothece decreased as salinity increased, and increased as temperature and nitrogen increased, and N. epithemioides increased as silica increased. Observed GSL phytoplankton relative abundances responded to environmental conditions as observed in the experiments, but correlations were weak except for chlorophytes, as diatoms and cyanobacteria relative abundances occasionally increased with unfavorable experimental conditions. The weak correlations between laboratory results and GSL observations could be due to the release of diatoms and cyanobacteria from microbialite biofilms in the lake’s benthos with cold stress and high winds, as a 5–10% release can produce diatom and cyanobacteria phytoplankton relative abundances of 24–48%. This suggests a novel potential link between GSL pelagic and benthic zones.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Demographic responses of an extremophile crustacean to environmental factors: Great Salt Lake (Utah, USA) brine shrimp (Artemia franciscana) - Gary E. Belovsky; Chad A. Larson; Heidi K. Mahon; Chad Mellison; Andrea C. Stumpf; Anghy Ramos Valencia (Hydrobiologia, 2025)
Hypersaline Great Salt Lake’s (GSL: Utah, USA) pelagic food web is dominated by the herbivore, Artemia franciscana . Artemia demographic responses (survival, developmental transition, and reproduction) to GSL salinities, temperatures, common phytoplankton and yeast, and food levels were examined by factorial experiment. Survival across developmental stages was best at 90 ppt salinity, and decreased as temperature increased. Transition between life stages was best at 45 ppt salinity, and increased as temperature increased. Food was most important with both survival and transitioning responding similarly to food types and increasing with amount of food. Artemia reproduce in two ways (diapausing cysts – oviparity, live young – ovoviviparity): ovoviviparous and total reproduction were greatest at 90 ppt salinity and 20 °C, while oviparous reproduction was weakly affected by salinity and greatest at 20 °C. Oviparity was greatest at low food availability, while ovoviviparity and total reproduction increased with food availability, so reproduction shifted from oviparity to ovoviviparity as food increased. Maternal effects were observed for cyst hatchability, and ovoviviparous nauplii survival and transitioning to the juvenile stage. Combinations of salinity, temperature, food taxa and food amount strongly affect demography, making single factor studies of limited value. Results explain Artemia abundance in different parts of GSL and among years.

Crossing the Pacific: Genomics Reveals the Presence of Japanese Sardine ( Sardinops melanosticta ) in the California Current Large Marine Ecosystem - Gary C. Longo; Jeremiah J. Minich; Nicholas Allsing; Kelsey James; Ella S. Adams‐Herrmann; Wes Larson; Nolan Hartwick; Tiffany Duong; Barbara Muhling; Todd P. Michael; Matthew T. Craig (Molecular Ecology, 2024)
Recent increases in frequency and intensity of warm water anomalies and marine heatwaves have led to shifts in species ranges and assemblages. Genomic tools can be instrumental in detecting such shifts. In the early stages of a project assessing population genetic structure in Pacific Sardine ( Sardinops sagax ), we detected the presence of Japanese Sardine ( Sardinops melanosticta ) along the west coast of North America for the first time. We assembled a high quality, chromosome‐scale reference genome of the Pacific Sardine and generated low coverage, whole genome sequence (lcWGS) data for 345 sardine collected in the California Current Large Marine Ecosystem (CCLME) in 2021 and 2022. Fifty individuals sampled in 2022 were identified as Japanese Sardine based on strong differentiation observed in lcWGS SNP and full mitogenome data. Although we detected a single case of mitochondrial introgression, we did not observe evidence for recent hybridization events. These findings change our understanding of Sardinops spp. distribution and dispersal in the Pacific and highlight the importance of long‐term monitoring programs.

Potato Seed Decay and Stand Loss is Not Caused by Dickeya Spread during Cutting and Handling of Seed Potatoes - Gary Secor; Viviana Rivera-Varas; Steve Johnson; Blake Greiner; Kal Larson; Amy Charkowski; Shaista Karim (American Journal of Potato Research, 2021)

Overwinter survival of crustacean diapausing cysts: Brine shrimp ( Artemia franciscana ) in Great Salt Lake, Utah - Gary E. Belovsky; Clay Perschon; Chad Larson; Chad Mellison; Jennifer Slade; Heidi Mahon; Hannah Appiah‐Madson; John Luft; Ryan Mosley; John Neill; Kyle Stone; Ashley Kijowski; et al. (Limnology and Oceanography, 2019)
Survivability of diapausing (cryptobiotic) life stages over time in nature, beyond maximum observed time for viability, is not well understood. Because these life stages are an adaptation to overcome harsh conditions, survivability over time is assumed to be high. Brine shrimp ( Artemia franciscana ) diapausing eggs (cysts) permit overwinter survival to initiate the population each spring. An experiment was designed to examine overwinter survival of brine shrimp cysts for 17 yr in Great Salt Lake (Utah, U.S.A.). Initial hatchability entering the winter (17.8–78.8%) and overwinter survivability (9.9–65.9%) of cysts varied dramatically among years. Better maternal nutrition increased initial hatchability. Overwinter survival of cysts decreased in part because some cysts hatch when it is too cold for the hatchlings to feed (0.8–39.4% among years), so they starve. However, overwinter cyst survival decreases the most with warmer waters in winter, and with better maternal nutrition, as both factors lead to diapause being easier to break. Annual variation in initial hatchability and survival is shown to be important to Great Salt Lake brine shrimp populations. Therefore, cryptobiotic life‐stage ecology needs to be better understood, as these life stages may have highly variable hatchability and survivability with normal environmental stresses.

Genetic diversity and population structure of sickleweed (Falcaria vulgaris; Apiaceae) in the upper Midwest USA - Sarbottam Piya; Madhav P. Nepal; Jack L. Butler; Gary E. Larson; Achal Neupane (Biological Invasions, 2014)

Production of Homozygous Transgenic Rainbow Trout with Enhanced Disease Resistance - Pinwen Peter Chiou; Maria J. Chen; Chun-Mean Lin; Jenny Khoo; Jon Larson; Rich Holt; Jo-Ann Leong; Gary Thorgarrd; Thomas T. Chen (Marine Biotechnology, 2014)

Exercise economy in African American and European American women - Gary R. Hunter; John P. McCarthy; Marcas M. Bamman; D. Enette Larson-Meyer; Gordon Fisher; Bradley R. Newcomer (European Journal of Applied Physiology, 2011)

Age, muscle fatigue, and walking endurance in pre-menopausal women - Gary R. Hunter; C. Scott Bickel; Pedro Del Corral; Nuala M. Byrne; Andrew P. Hills; D. Enette Larson-Meyer; Marcas M. Bamman; Bradley R. Newcomer (European Journal of Applied Physiology, 2011)

Seasonal nutrient and plankton dynamics in a physical-biological model of Crater Lake - Katja Fennel; Robert Collier; Gary Larson; Greg Crawford; Emmanuel Boss (Hydrobiologia, 2007)

Measurements of spectral optical properties and their relation to biogeochemical variables and processes in Crater Lake, Crater Lake National Park, OR - Emmanuel S. Boss; Robert Collier; Gary Larson; Katja Fennel; W. S. Pegau (Hydrobiologia, 2007)

Distribution and abundance of zooplankton populations in Crater Lake, Oregon - Gary L. Larson; C. David McIntire; Mark W. Buktenica; Scott F. Girdner; Robert E. Truitt (Hydrobiologia, 2007)

Bacterioplankton communities of Crater Lake, OR: dynamic changes with euphotic zone food web structure and stable deep water populations - Ena Urbach; Kevin L. Vergin; Gary L. Larson; Stephen J. Giovannoni (Hydrobiologia, 2007)

Predicting Secchi disk depth from average beam attenuation in a deep, ultra-clear lake - Gary L. Larson; Robert L. Hoffman; Bruce R. Hargreaves; Robert W. Collier (Hydrobiologia, 2007)

Long-term limnological research and monitoring at Crater Lake, Oregon - Gary L. Larson; Robert Collier; Mark Buktenica (Hydrobiologia, 2007)

Variability of kokanee and rainbow trout food habits, distribution, and population dynamics, in an ultraoligotrophic lake with no manipulative management - Mark W. Buktenica; Scott F. Girdner; Gary L. Larson; C. David McIntire (Hydrobiologia, 2007)

Seasonal and interannual variability in the taxonomic composition and production dynamics of phytoplankton assemblages in Crater Lake, Oregon - C. David McIntire; Gary L. Larson; Robert E. Truitt (Hydrobiologia, 2007)

Thermal, chemical, and optical properties of Crater Lake, Oregon - Gary L. Larson; Robert L. Hoffman; David C. McIntire; Mark W. Buktenica; Scott F. Girdner (Hydrobiologia, 2007)

Effects of upstream lakes on dissolved organic matter in streams - James H. Larson; Paul C. Frost; Zhiyu Zheng; Carol A. Johnston; Scott D. Bridgham; David M. Lodge; Gary A. Lamberti (Limnology and Oceanography, 2007)
We examined the effects of upstream lakes on dissolved organic matter (DOM) quantity and the absorbance of ultraviolet (UV) radiation in the streams of northern Michigan. We assessed DOM concentration and absorbance in 15 streams with upstream lakes and 17 streams without upstream lakes located in the same geographic region in May and August 2003. In addition, we estimated watershed land cover and morphology to assess the possibility that other landscape variables could account for DOM differences between the two stream types. The concentration of dissolved organic carbon, its UVB absorbance, and its molar absorbtivity (absorbance per unit carbon) were all significantly lower in streams with upstream lakes than in streams with no lakes. Strong predictive relationships existed between upstream watershed metrics and stream DOM properties, but varied by season and the presence of upstream lakes. DOM quantity and UV‐absorbing ability were related to different watershed metrics, with DOM quantity being strongly related to terrestrial watershed metrics, whereas UV‐absorbing ability was most strongly related to percent water surface area. Upstream lakes strongly influence downstream DOM potentially because of their long water residence times, which could increase opportunities for DOM processing. Upstream lakes represent a strong landscape predictor of stream DOM properties that is not directly tied to terrestrial DOM sources and processing.

Landscape predictors of stream dissolved organic matter concentration and physicochemistry in a Lake Superior river watershed - Paul C. Frost; James H. Larson; Carol A. Johnston; Katie C. Young; Patricia A. Maurice; Gary A. Lamberti; Scott D. Bridgham (Aquatic Sciences, 2006)

Landscape predictors of stream dissolved organic matter concentration and physicochemistry in a Lake Superior river watershed - Paul C. Frost; James H. Larson; Carol A. Johnston; Katie C. Young; Patricia A. Maurice; Gary A. Lamberti; Scott D. Bridgham (Aquatic Sciences, 2006)

Inverse relationship between exercise economy and oxidative capacity in muscle - Gary R. Hunter; Marcas M. Bamman; D. Enette Larson-Meyer; Denis R. Joanisse; John P. McCarthy; Tamilane E. Blaudeau; Bradley R. Newcomer (European Journal of Applied Physiology, 2005)

Persistence of an unusual pelagic zooplankton assemblage in a clear, mountain lake - Gary L. Larson; Robert L. Hoffman; C. David McIntire (Hydrobiologia, 2002)

Unusual bacterioplankton community structure in ultra‐oligotrophic Crater Lake - Ena Urbach; Kevin L. Vergin; Lei Young; Ariel Morse; Gary L. Larson; Stephen J. Giovannoni (Limnology and Oceanography, 2001)
The bacterioplankton assemblage in Crater Lake, Oregon (U.S.A.), is different from communities found in other oxygenated lakes, as demonstrated by four small subunit ribosomal ribonucleic acid (SSU rRNA) gene clone libraries and oligonucleotide probe hybridization to RNA from lake water. Populations in the euphotic zone of this deep (589 m), oligotrophic caldera lake are dominated by two phylogenetic clusters of currently uncultivated bacteria: CL120–10, a newly identified cluster in the verrucomicrobiales, and ACK4 actinomycetes, known as a minor constituent of bacterioplankton in other lakes. Deep‐water populations at 300 and 500 m are dominated by a different pair of uncultivated taxa: CL500–11, a novel cluster in the green nonsulfur bacteria, and group I marine crenarchaeota. b‐Proteobacteria, dominant in most other freshwater environments, are relatively rare in Crater Lake (

Integrating Physical and Chemical Characteristics of Lakes into the Glacially Influenced Landscape of the Northern Cascade Mountains, Washington State, USA - Gary L. Larson; Gregg Lomnicky; Robert Hoffman; William J. Liss; Elizabeth Deimling (Environmental Management, 1999)

Interaction between Introduced Trout and Larval Salamanders (Ambystoma macrodactylum) in High-Elevation Lakes - Torrey Tyler; William J. Liss; Lisa M. Ganio; Gary L. Larson; Robert Hoffman; Elisabeth Deimling; Gregg Lomnicky (Conservation Biology, 1998)

Interaction between Introduced Trout and Larval Salamanders ( Ambystoma macrodactylum ) in High‐Elevation Lakes - Torrey Tyler; William J. Liss; Lisa M. Ganio; Gary L. Larson; Robert Hoffman; Elisabeth Deimling; Gregg Lomnicky (Conservation Biology, 1998)
The larval stage of the long‐toed salamander (Ambystoma macrodactylum) is the top vertebrate predator in high‐elevation fishless lakes in the North Cascades National Park Service Complex, Washington (U.S.A.). Although most of these high‐elevation lakes were naturally fishless, trout have been stocked in many of them. We sought to determine the effects of physicochemical factors and introduced trout on abundance and behavior of A. macrodactylum larvae. Larval salamander densities were estimated by snorkeling. Snorkelers carefully searched through substrate materials within 2 m of the shoreline and recorded the number of larvae observed and if larvae were hidden in benthic substrates. Physicochemical factors were measured in each lake on the same day that snorkel surveys were conducted. In fishless lakes, larval salamander densities were positively related to total Kjeldahl‐N concentration and negatively related to lake elevation. Crustacean zooplankton, especially cladocerans, were important food resources for larval A. macrodactylum. Crustacean zooplankton and cladoceran densities were positively related to total Kjeldahl‐N, suggesting that increased food resources contributed to increased densities of larval A. macrodactylum. Differences in larval salamander densities between fish and fishless lakes were related to total Kjeldahl‐N concentrations and the reproductive status of trout. Mean larval salamander densities for fishless lakes with total Kjeldahl‐N Interacción entre una Trucha Introducida y Larvas de la Salamandra ( Ambystoma macrodactylum ) en Lagos de Alta Elevación Los estados larvales de la salamandra Ambystoma macrodactylum están entre los depredadores mayores en lagos de alta elevación carentes de peces del North Cascades National Park Service Complex del estado de Washington, en los Estados Unidos. Aunque la mayoría de estos lagos de alta elevación careciéron de peces de manera natural, en varios de ellos se han introducido artificialmente truchas. Nos propusimos determinar los efectos de factores fisico‐químicos y la trucha introducida en la abundancia y conducta de larvas de A. macrodactylum. Las densidades de las larvas fuéron estimadas buceando con snorquel. Los buzos cuidadozemente muestrearon los materiales del substrato dentro de los 2 m a la orilla y anotaron el número de larvas observadas, además de observar si las larvas se encontraban escondidas en substratos bénticos. Los factores fisico‐químicos fueron medidos en cada lago el mismo dia que se realizaron los muestreos de larvas. En lagos sin peces, las densidades de larvas de salamandras se relacionaron positivamente con la concentración total de N‐Kjendahl y negativamente con le elevación del lago. Crustáceos zooplanctónicos, especialmente cladóceros fueron fuentes importantes de recursos para las larvas de A. macrodactylum. Los crustáceos zooplanctónicos y la densidad de cladóceros estuvieron positvamente correlacionados con N‐Kjendahl total, sugiriendo que los incrementos en recursos alimenticios contribuyeron con el incremento en las densidades de larvas. Las diferencias en la densidad de larvas de salamandras entre lago con y sin peces estuvieron relacionadas con las concentraciones de N‐Kjendahl total y el estatus reproductivo de la trucha. La densidad promedio de larvas de salamandras en lagos sin peces con un total de N‐Kjendahl